Endogenous androgens and risk of epithelial ovarian cancer: results from the European Prospective Investigation into Cancer and Nutrition (EPIC). - Rinaldi, S; Dossus, L; Lukanova, A; Peeters, P; Allen, N; Key, T; Bingham, S; Khaw, K; Trichopoulos, D; Trichopoulou, A; Oikonomou, E; Pera, G; et al. (2007)
Few epidemiologic studies have examined the hypothesis that circulating androgens are involved in the development of ovarian cancer. We investigated the association between prediagnostic serum levels of androgens and sex hormone-binding globulin (SHBG) and ovarian cancer risk in a case-control study nested within the European Prospective Investigation into Cancer and Nutrition cohort. One hundred and ninety-two ovarian cancer cases and 346 matched controls not using exogenous hormones at baseline blood donation were eligible for the study. Serum levels of testosterone, androstenedione, dehydroepiandrosterone sulfate, and SHBG were measured by direct immunoassays. Free testosterone (fT) was calculated according to mass action laws. Multivariate conditional logistic regression was used to estimate odds ratios adjusted for possible confounders. Overall, there was no association between serum concentrations of androgens or SHBG and ovarian cancer risk. In postmenopausal women, fT concentrations were inversely related to risk [highest versus lowest tertile odds ratio 0.45 (0.24-0.86); P(trend) = 0.01]. Among women diagnosed before the age of 55 years, there was a negative association with SHBG and a positive association with fT and ovarian cancer risk, although these associations were not statistically significant. The present study suggests that circulating androgens and SHBG levels are not strongly associated with ovarian cancer risk, although levels of fT may be associated with an increased risk among women diagnosed at relatively young age. The heterogeneity of results on the associations of fT with ovarian cancer risk in postmenopausal women deserves further investigation.